Conceptualizing Systems for Understanding - Burton-JonesAndrew; MesoPeter, N (Information Systems Research, 2006)
During the early phase of systems development, systems analysts often conceptualize the domain under study and represent it in one or more conceptual models. One of the most important, yet elusive ...